Tabagismo passivo e a ocorrência de dificuldades de aprendizagem em escolares do ensino fundamental no município de Campo Verde - MT - Jorge, Juliana Gomes (2013)
Exposure to passive smoking constitutes a major public health problem. The environmental tobacco smoke affects many physiological processes as well as cognitive functions related to learning. Objective: To analyze the association of smoking during pregnancy and in the home acquisition and/or development of learning in school children of elementary school in the municipality of Campo Verde – Mato Grosso. Methods: We carried a cross-sectional epidemiological study. Participants consisted of a representative sample of the population of students from 785 2nd to 5th elementary school. Students were evaluated by the Protocol School Literacy Screening, to identify the presence of learning difficulties. Mothers / caregivers were interviewed using a structured questionnaire containing questions relating to household smoking. Analyses Descriptive, bivariate, and logistic regression. A descriptive analysis was performed by means of tables and description of the findings. In bivariate associations were identified by calculating the crude prevalence ratio (PR) and their confidence intervals of 95% (95%), calculating the statistical significance of the association using the chi-square test for prevalence ratio with the 95% confidence by the Mantel-Haenszel method (95%), or Fisher exact test when indicated. In logistic regression were considered all variables that showed a statistically significant association from the crude analyzes, with a p-value less than 0.20, remaining in the final model variables with a significance level less than or equal to 0.05 or those considered of importance, according to the literature. Data were analyzed using SPSS statistical software for Windows version 15.0, EPI INFO 2000 version 3.5.1 and STATA version 9.0. Result: The bivariate analysis showed a significant association for the variables Gender, Education and Race / Color School, Education, Race / Color, Marital Status and Economy Class Mothers, Number of Prenatal Consultations, Low Birth Weight and Usage alcohol, Tobacco Current Maternal, gestational and during breastfeeding, and Otitis for variables related to factors associated with learning. In the final model of logistic regression was considered statistically significant variable household smoking. Conclusion: The study showed an association between exposure to passive smoking and learning difficulties in schools children.